1995
DOI: 10.1111/j.1600-051x.1995.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐blind studies of the effects of improved periodontal health on metabolic control in Type 1 diabetes mellitus

Abstract: Uncontrolled studies have suggested a beneficial effect of periodontal treatment on metabolic control of insulin-dependent diabetes mellitus (IDDM). We therefore conducted controlled single-blind studies, using current metabolic status indicators in IDDM subjects free of significant complications other than periodontal diseases. In the 1st study, 41 IDDM subjects with gingivitis and early periodontitis were randomly assigned to treatment (oral hygiene and scaling) or control groups. The study was completed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 25 publications
(17 reference statements)
5
101
1
2
Order By: Relevance
“…It has been shown that periodontal infections can change the metabolic-endocrine status of the host, leading to difficulties in the control of blood sugar levels, which can contribute to insulin-resistance, hyperglycemia and complications in the metabolic control of diabetes mellitus 2,11,15 . Moreover, periodontal treatment improves diabetes control 2 . Therefore, periodontal infection control could be one additional important tool used in the metabolic control of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that periodontal infections can change the metabolic-endocrine status of the host, leading to difficulties in the control of blood sugar levels, which can contribute to insulin-resistance, hyperglycemia and complications in the metabolic control of diabetes mellitus 2,11,15 . Moreover, periodontal treatment improves diabetes control 2 . Therefore, periodontal infection control could be one additional important tool used in the metabolic control of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that severe periodontitis may be an important risk factor in the progression of diabetes, and control of periodontal infection is essential to achieve long-term control of diabetes mellitus. Grossi and Genco (46) reexamined the studies that addressed the effect of periodontal treatment on metabolic control of diabetes mellitus (1,16,47,95,124,132,149). Six of these studies included type 1 patients, and two studies (16,47) included type 2 patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Full texts of these 23 studies were obtained and evaluated. Collectively, we selected 11 intervention studies as final candidates satisfying our inclusion criteria set a priori (Table 1) (Miller et al, 1992;Seppala and Ainamo, 1994;Aldridge et al, 1995;Smith et al, 1996;Westfelt et al, 1996;Grossi et al, 1997;Christgau et al, 1998;Iwamoto et al, 2001;Stewart et al, 2001;Rodrigues et al, 2003). One of these 11 studies (Smith et al, 1996) could not provide a numeric value of HbA1c and was excluded from analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%